KIT, PDGFRA, and BRAF Mutational Spectrum Impacts on the Natural History of Imatinib-naive Localized GIST: A Population-based Study. (July 2015) - Rossi, Sabrina; Gasparotto, Daniela; Miceli, Rosalba; Toffolatti, Luisa; Gallina, Giovanna; Scaramel, Enrico; Marzotto, Alessandra; Boscato, Elena; Messerini, Luca; Bearzi, Italo; Mazzoleni, Guido; Capella, Carlo; et al.
Abstract : The mutation status of KIT or PDGFRA notoriously affects the response of advanced gastrointestinal stromal tumors (GISTs) to tyrosine kinase inhibitors. Conversely, it is currently still unclear whether mutation status impinges on the prognosis of localized, untreated GISTs. Hence, at present, this variable is not included in decision making for adjuvant therapy. A series of 451 primary localized GISTs were analyzed for KIT, PDGFRA, and BRAF mutations. Univariable and multivariable analyses and a backward selection procedure were used to assess the impact of mutation status on overall survival and to identify prognostically homogenous groups. Mutation was a significant prognostic indicator of overall survival in naive, localized GISTs ( P <0.001): KIT -mutated patients had a worse outcome than PDGFRA -mutated or triple-negative ( KIT, PDGFRA, BRAF wild-type) cases. Multivariable Cox regression models allowed us to identify 3 molecular risk groups: group I exhibited the best outcome and included PDGFRA exon 12, BRAF, and KIT exon 13-mutated cases; group II, of intermediate clinical phenotype (HR=3.06), included triple-negative, KIT exon 17, PDGFRA exon 18 D842V, and PDGFRA exon 14-mutated cases; group III displayed the worst outcome (hazard ratio=4.52), and comprised KIT exon 9 and exon 11 and PDGFRA exon 18 mutations apart from D842V. This study highlights the prognostic impact of mutation status on the natural course of GIST and suggests that the molecular prognostic grouping may complement the conventional clinicopathologic risk stratification criteria in decision making for adjuvant therapy. Abstract : Supplemental Digital Content is available in the text.